(3Yjf GdEUGHI ajeG ESJOQcJg YGFTI Ydi GdUMGHIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3eMjj GdOjf Hf RcQjG jMji Hf TQa, GHf eQj GdfhGhj,J (B676 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai hHYO agPG LRA dNUJ ajg cJGH GdELGHI dEjQGO eG ESJOQcJg YGFTI Ydi GdUMGHI ddEeGe HOQ GdOjf GdRQcTi bdJ dYGFTI bO CNP GdSff Yf QShd Gddg Udi Gdgd Ydjg hSde s
(3BNQgG (B:s
(3hbGd GHf CHj TjHI MOKfG GHf YjjfI Yf YHO GdQMef Hf bGSe Yf GHjg Yf YGFTI cGfJ JeTi ai Na hGMO hJbhd GdCNbf CHGgQjQI hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdeLGejYs